Lanthanide MOFs constructed based on a difunctional ligand with bimodal emission and Eu3+ doped Dy3+ materials: white emission and color tuning. Issue 86 (1st September 2016) - Xiao, Peng; Wang, Ping; Fan, Rui Qing; Du, Xi; Chen, Wei; Zhang, Hui Jie; Song, Yang; Yang, Yu Lin
Abstract : A new strategy for multicolor materials by Dy and Eu cations. Abstract : Based on azabicyclo ligands, four 3D supramolecular lanthanide complexes have been synthesized through hydro(solvo)thermal reactions, generally formulated as [Dy(bipy) (NO3 )3 ]2 (1·Dy ), [Dy(bipy)2 (NO3 )3 ] (2·Dy ), [Dy2 (bpdc)3 (DMF)(H2 O)]2 ·(DMF)10 (H2 O) (3·Dy ) and [Eu4 (bpdc)6 (CH3 NH2 )3 (DMSO)(H2 O)] (4·Eu ) (Bipy = 2, 2′-bipyridine; H2 bpdc = 2, 2′-bipyridine-5, 5′-dicarboxylic acid, DMF = N, N -dimethylformamide), and structurally characterized by single-crystal X-ray diffraction, IR spectroscopy, elemental analysis and powder X-ray diffraction (PXRD). There are three kinds of hydrogen bonding, C2–H2A⋯O6, C4–H4A⋯O4 and C8–H8A⋯O8 along the a / c, b, c axis, respectively in complex1·Dy . They connect the1·Dy complex into a 3D 6-connected pcu supramolecular network.2·Dy is connected into a 3D network with 8–connected bcu architecture by two kinds of hydrogen bonding: C2–H2A⋯O1 and C9–H9A⋯O3. In order to connect the polymer to form a 3D complex, H2 bpdc has been chosen in the synthesis and design of the crystal. In the network of3·Dy, two kinds of Dy(iii ) cations in different coordination models construct the different binuclear [Dy2 O14 (DMF)2 ] and [Dy2 O12 (H2 O)2 ], and further form the (4, 4, 6)-connected 3D architecture. The isostructural complex4·Eu has been synthesised simultaneously. The property of luminescence in solid state or different solvents of the four complexes has been studied in detail. The four complexes show the unique emission peaks of lanthanide cations. Futhermore, in3·Dy and4·Eu, the ligand shows a rare bimodal emission, which can sensitize the emission of europium cations as an "antenna effect", and the shorter one keeps its blue emission though coordinated with Dy(iii ) cations. Based on the synthesis of green or red color materials, multicolored photoluminescence tuning has been studied in detail through growth of a series of bimetallic complexes, the crystal formula as [Dy2 n Eu′2−2 n (bpdc)3 (DMF)(H2 O)] (M-1–M-9 ; 0 < n < 1). We achieved dichromatic fine-tuning among the triangle region of red, green and white. The linear dependence of the emissions has been analyzed, and the mathematical matrix model is useful to calculate the ratio and excitation wavelength for a given color in need.